GROWTH OF THE PEDIATRIC KNEE MENISCUS: A CADAVERIC STUDY. Issue 7 (30th July 2021) - Vuong, Brian; Segovia, Nicole; Randhawa, Sahej; Trivedi, Sunny; Tran, Emily; Ganley, Theodore; Ellis, Henry; Wilson, Philip; Fabricant, Peter; Shea, Kevin
Background: The menisci of the knee play a critical role in maintaining structural integrity, as well as in load bearing and shock absorption. In adolescent patients, meniscal tear is a very common sports injury, and is frequently associated with concomitant traumatic injuries including tibial eminence fracture or ACL tear. The incidence of pediatric meniscal tears is increasing, and anatomic studies to guide repair, saucerization and transplantation do not exist. Hypothesis/Purpose: This study's purpose was to evaluate meniscus dimensions in the developing meniscus and provide anatomic parameters for repair, saucerization, resection, transplantation. Methods: From images of 29 dissected cadaveric knee specimens between 1 month and 132 months of age obtained on a copy stand (14 left knee, 15 right knee), we made direct length measurements from the inner to outer meniscus rim at 45 degree intervals (12, 1:30/10:30, 3:00/9:00, 4:30/7:30 o'clock, 6 o'clock) using Autodesk Fusion 360 software (Figure 1.1). We also measured width between the outer medial and lateral meniscus rims, as well as CT measurements of coronal and sagittal width of the tibial plateau using OsiriX DICOM software. Generalized linear models were used to evaluate the associations of meniscal length measurements with age, tibial width, and meniscal width measurements. All statistical analyses were completed with a two-sided level of significance of 0.05. Results: All radial length measurements were predicted to increase significantly with age (p < 0.01), as coronal tibial width increases (p < 0.05), and as lateral-medial meniscal width increases (p < 0.001) (Figure 1.2). Other than the lateral 3 o'clock measurement (p = 0.119), all radial measurements were predicted to increase significantly as sagittal tibial width increases (p < 0.05). The posterior zones of the medial meniscus (6:00, 4:30/7:30) were found to increase in radial length at a faster rate than the anterior zones. The anterior zones of the medial meniscus (12:00, 1:30/10:30) had the slowest rate of growth. Discussion/Conclusion: Meniscus radial length is related to age, tibial plateau width, and lateral-medial meniscus width. Radial dimensions from normal lateral menisci may allow the surgeon to obtain ideal size of resection, saucerization of discoid menisci. The growth of medial meniscus posterior zones is greater than the anterior zones. This may be attributed to increased posterior region load bearing which increases with ambulation in the developing child. Improved anatomic understanding may help surgeons plan for discoid resection/saucerization/repair, and also support appropriate selection of meniscus allograft for transplantation. Figure 1.1. Figure 1.2.